Single tooth replacement using a ceramic resin bonded fixed partial denture: A case report - Kara, Haluk Baris; Aykent, Filiz (European Journal of Dentistry, 2012)
This article describes the use of an all ceramic resin-bonded ﬁxed partial denture as a conservative solution for the replacement of an incisor. It is a minimally invasive technique that does not discolor the abutment teeth. (Eur J Dent 2012;6:101-104)
Keywords: Minimally invasive technique; IPS Empress 2; replacement of mandibular lateral incisor; resin bonded fixed partial denture